Syndemic: tautology and dichotomy in a new-old concept - Souza, Diego de Oliveira (2023)
In the wake of the decade’s most severe pandemic, the term ‘syndemic’ reemerged as an alternative to  better designate the nature assumed by COVID-19.  The authors who advocate for this concept argue that it gives greater analytical breadth, which allows an  understanding of the synergistic interactions between diseases and their social origins. This essay aims to  analyze this concept in the light of historical-dialectical materialism. In particular, it dialogues with  the Collective Health current developed under the  influence of Marxism. Thus, the category of social  determination of the health-disease process is called  to the debate when its greater breadth is revealed  before the syndemic concept. We found that the  concept under analysis is tautological and reproduces  old dichotomies of the biomedical model while  criticizing it.